The right to an audience at court: Realities, risks and challenges. A qualitative study from the perspective of practitioners working in a Community Rehabilitation Company. (September 2019) - Woolford, Rebecca; Salami, Peter
A fundamental role of the probation service is to provide advice and information to courts assisting in determining the most appropriate sentencing decisions. Historically, all probation officers as part of their mandatory training had experience in a court setting. Under the government's Transforming Rehabilitation (TR) reforms, probation services were divided into 21 new privately-owned Community Rehabilitation Companies (CRCs) and a new public National Probation Service (NPS). This resulted in the NPS assuming the right to an audience at court by statute and the withdrawal of a right to an audience at court for CRCs. This qualitative study conducted during the summer of 2017 seeks to gain an insight into the views of CRC practitioners on contemporary court practice, specifically exploring their views on not having a professional role to provide advice and information on their caseload in court. The interviews identified four themes, reflecting both barriers to, and facilitators of, the withdrawal of the right to an audience at court by the CRC. These themes illustrated that the initial developments in the courts post-TR did not give the opportunity for active CRC involvement, resulting in increased scrutiny and criticism of their practice.